Preparation and Characterization of Oil Palm Tree for Insulation Material - Elias, Nur Amirah; Othman, Siti Amira (International Journal of Sustainable Construction Engineering and Technology, 2022)
The most important commodity from Malaysia is the oil palm tree, which has helped to reshape the agricultural and economic landscape. Oil palm tree pieces are used to make cellulose biomass. However, the current state of oil palm waste has created a significant disposal issue. Waste management is based on the ideas of waste minimization and recycling. In order to achieve energy efficient and environmentally friendly, oil palm tree is the best choice. due to some problems occurring from previous studies which is fiberglass, cellulose has been made a new idea for insulation. The effectiveness of the insulation method is measured in R-value. R-value determines the ability of heat to pass through the insulator. If the fiberglass has been installed for a long period of time, the R-value will decrease as the insulation settles or compacts. The purpose of this study was to study the effect of ionizing radiation on cellulose using time-varying method, to identify the chemical and physical properties of oil palm tree and lastly, to identify the resistivity for cement and cellulose mixture. In view of the fact, cellulose contain no oxygen due to material’s compactness. Considering, there is no oxygen in the materials, the amount of damage cause by fire can be reduced. In this research, it will undergo pre- treatment method to obtain the cellulose. After that, the sample will go through four-point probe method to earn the resistivity. Considering that the finding has been proven by the result of the resistivity. In summation, the cellulose from oil palm tree can be propose as the new insulating material in the building structure.